Innovative Teaching Methods - Maxmudjanova Diana Kahramonovna (Research Parks Publishing LLC, 2021)
Innovative teaching methods make it possible to form the experience of students' creative and innovative activities, which ultimately affects the competence of the future specialist. The essence of innovation in teaching, the innovative teaching methods themselves, in our opinion, is also determined by their dynamism and activity.